2020
DOI: 10.3390/molecules25204841
|View full text |Cite
|
Sign up to set email alerts
|

Pimpinella anisum Essential Oil Nanoemulsion Toxicity against Tribolium castaneum? Shedding Light on Its Interactions with Aspartate Aminotransferase and Alanine Aminotransferase by Molecular Docking

Abstract: The insecticidal activity is the result of a series of complex interactions between toxic substances as ligands and insect’s enzymes as targets. Actually, synthetic insecticides used in pest control programs are harmful to the environment and may affect non-target organisms; thus, the use of natural products as pest control agents can be very attractive. In the present work, the toxic effect of aniseed (Pimpinella anisum L.) essential oil (EO) and its nanoemulsion (NE) against the red flour beetle Tribolium ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…Therefore, GML mass change during 2 days of feeding was provoked not only by among-treatment variation in the amount of consumed and assimilated food (pre-ingestive and pre-digestive mechanisms, respectively) but also was a consequence of the EO influence on post-ingestive and post-digestive mechanisms. Our results are in accordance with findings of other studies which showed negative values of RGR and ECI in T. castaneum adults exposed to anise EO [ 45 ] and 4th instar P. unipuncta larvae exposed to trans-anethol [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, GML mass change during 2 days of feeding was provoked not only by among-treatment variation in the amount of consumed and assimilated food (pre-ingestive and pre-digestive mechanisms, respectively) but also was a consequence of the EO influence on post-ingestive and post-digestive mechanisms. Our results are in accordance with findings of other studies which showed negative values of RGR and ECI in T. castaneum adults exposed to anise EO [ 45 ] and 4th instar P. unipuncta larvae exposed to trans-anethol [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…Depletion of metabolites and adaptive increase in antioxidative and detoxification enzymes have been described in pest insects exposed to EOs [ 114 , 122 , 123 , 124 , 125 , 126 ] and azadirachtin [ 127 , 128 ]. Similar results were obtained in studies dealing with the impact of Apiaceae EOs on insect pests [ 45 , 113 , 129 , 130 , 131 ]. In lepidopteran pests, S. frugiperda and Anticarsia gemmatalis Hübner limonene, carvon, estragol and anethol (compounds of anise, dill and fennel seed EOs) are detoxified by microsomal cytochrome P-450 monooxygenases [ 132 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…47 Linalool has antifeedant activity against the red flour beetle (Tribolium castaneum). 46 These data show that linalool has application prospects in the control of sanitary and agricultural pest insects. An EO of Pimenta dioica that contains linalool as a main component can completely inhibit the mycelial growth of Aspergillus flavus at 2.5 mg/L.…”
Section: ■ Frequently Studied Monoterpenes With Pesticidal Activitiesmentioning
confidence: 92%
“…Several studies on natural bioinsecticides have revealed that essential oils along with other secondary plant metabolites (terpenoids, polyphenols, steroids, and alkaloids) synthesized by aromatic and medicinal plants are responsible for several biological activities against plant pests, especially essential oils which have shown important insecticidal, nematicidal, acaricidal, and larvicidal properties [10][11][12][13][14][15][16][17][18][19][20]. Essential oils not only act as poisons or neurotropic on the nervous system of insects [21][22][23] but also can affect cytochrome P450, which plays a key role in the insect detoxification system, alter insect metabolism (e.g., ATP synthesis, Krebs cycle, oxidative phosphorylation, and others) [24]. Overall, the final action of EOs may be the result of more than one specific interaction with the targets, so that the possibility of insects developing resistance is greatly reduced [25].…”
Section: Introductionmentioning
confidence: 99%